2013
DOI: 10.1098/rsbl.2013.0057
|View full text |Cite
|
Sign up to set email alerts
|

Jaws for a spiral-tooth whorl: CT images reveal novel adaptation and phylogeny in fossil Helicoprion

Abstract: New CT scans of the spiral-tooth fossil, Helicoprion, resolve a longstanding mystery concerning the form and phylogeny of this ancient cartilaginous fish. We present the first three-dimensional images that show the tooth whorl occupying the entire mandibular arch, and which is supported along the midline of the lower jaw. Several characters of the upper jaw show that it articulated with the neurocranium in two places and that the hyomandibula was not part of the jaw suspension. These features identify Helicopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…11,18 An ancient cartilaginous fish genus, Helicoprion, even had its mandibular teeth arranged in a spiral whorl. 20 Theodore Cook, in his book The Curves of Life, quoted Alfred Wallace, one of the fathers of modern evolutionary theory, as saying, "the basic condition of the exquisite forms in nature, (is) never producing straight lines but an endless variety of curves, and spirals." 3 Curves and spirals are nature's economical way of accommodating growth to produce effective functional form.…”
Section: Biologic Examples Of Fibonacci Numbers and The Golden Ratiomentioning
confidence: 98%
“…11,18 An ancient cartilaginous fish genus, Helicoprion, even had its mandibular teeth arranged in a spiral whorl. 20 Theodore Cook, in his book The Curves of Life, quoted Alfred Wallace, one of the fathers of modern evolutionary theory, as saying, "the basic condition of the exquisite forms in nature, (is) never producing straight lines but an endless variety of curves, and spirals." 3 Curves and spirals are nature's economical way of accommodating growth to produce effective functional form.…”
Section: Biologic Examples Of Fibonacci Numbers and The Golden Ratiomentioning
confidence: 98%
“…The tooth whorl has been widely depicted as spiraling upward or downward from the jaws or as defense structures emanating from dorsal fins and tail (Woodward, ; Karpinsky, , ; Simoens, ; Hay, ; John, ; Obruchev, ; Eaton, ; Bendix‐Almgreen, ; Matsen and Troll, ; Purdy, ; Carr, ). Recently, CT‐scans of a fossil Helicoprion , specimen IMNH 37899, revealed that the jaws were imbedded deeper inside the rock (Tapanila et al, ; Fig. A).…”
Section: Introductionmentioning
confidence: 99%
“…A). The jaws were articulated and surrounded the tooth whorl in a naturally closed position (Tapanila et al, ; Fig. B,C).…”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary "lawn-mower" dental battery of Nigersaurus (Figure 1), adapted to an herbivorous diet is trumped for deviant dentitions by the bizarre spiral tooth whorl in the fossil Helicoprion [10] (Figure 2). …”
Section: Comparative Odontologymentioning
confidence: 99%